National audit of antidote stocking in acute hospitals in the UK. Issue 5 (8th August 2012) - Thanacoody, Ruben H K; Aldridge, Gloria; Laing, Willie; Dargan, Paul I; Nash, Stephen; Thompson, John P; Vale, Allister; Bateman, Nick; Thomas, Simon
Abstract : Background: Inadequate stocking of essential antidotes in hospitals for the treatment of poisoned patients has been reported worldwide. Joint National Poisons Information Service (NPIS)/College of Emergency Medicine (CEM) guidelines for antidote stocking in UK emergency departments and acute hospitals were published in 2008. Aim: To determine the impact of these guidelines by surveying the availability of antidotes in acute hospitals in the UK. Methods: A two-page questionnaire consisting of antidote stocking information was distributed in 2010 to the Chief Pharmacist in all acute hospitals in the UK. The availability of 28 antidotes in the NPIS/CEM antidote guidelines as well as that of Intralipid was surveyed. Results: Surveys were completed for 196 of the 224 (87.5%) hospitals. Over 90% of hospitals had acetylcysteine, activated charcoal, dantrolene, desferrioxamine, naloxone, flumazenil and vitamin K available within the recommended time period. Pralidoxime was reported to be held in only 33% of hospitals, though pralidoxime is supplied by the Department of Health to 95 hospitals in the UK that act as holding centres. Cyproheptadine and viper venom antiserum were held in around 50% of acute hospitals. For the treatment of cyanide and toxic alcohol poisoning, more than one antidote is available. For cyanide poisoning, most hospitals held at least one antidote (usually dicobalt edetate) but 9 (5%) held none of the four antidotes. For toxic alcohol and glycol poisoning, most hospitals held ethanol for intravenous use but not fomepizole and 30 (15%) did not stock any antidote for toxic alcohol poisoning. Conclusion: Stocking of less commonly used antidotes is inconsistent. This is likely to result in delayed access to treatment and worse patient outcomes.